Clifford's Ethic of Belief and Maximum Extreme Reasoning - Ghasem Pourhassan; Afsaneh Pandjoo (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The deontological epistemic approach was a reaction to the foundationalism approach that advocated the existence of basic or self-justified beliefs. Descartes, skeptical of any kind of knowledge, provided the first foundations for such an approach. John Locke and W. K. Clifford expanded it with two different perspectives. Locke, in "The Reasonableness of Christianity" and "Human Understanding" and Clifford in "The Ethic of Belief" attempted to form extreme reasoning approach while criticizing foundationalism and emphasizing the existence of reason for any belief. This view provided a new basis for the acceptance of belief, which emphasized both reasoning and the ethical aspect of accepting the belief. Clifford in the treatise of "The Ethic of Beliefs", by telling two specific stories, while criticizing and praising current epistemology, seeks to show that the importance of ethical consequences of epistemic belief is more than merely justification. His major point of reliance in this path is the link between ethics and epistemology. In his treatise, he criticized the religious rightness beliefs of Muslims and, after Locke, specifically addressed the theory of authority. Clifford's method will face many challenges in emphasizing mere reason of maximum extreme type, and rejection of the particular state of faith.